1971
DOI: 10.1055/s-0028-1099672
|View full text |Cite
|
Sign up to set email alerts
|

STUDIES ONTAXUS BACCATA– I. Preliminary Phytochemical and Behavioral Investigations

Abstract: V o h o r a and I s h w a r K u m a rTaxtrs baccata, L i n n . (Taxaceae), is reputed to possess varied medicinal properties eg. carminative, cardiotonic, expectorant, anti-spasnlodic, diuretic, antiseptic, emmenagogue etc. ( K i r t i k a r and B a s u , 1933; N a d a k a r n i , 1954; C h o p r a et al., 1958). Aqueous extract of the leaves has been reported to elicit encouraging (55%) anti-implantation activity in albino rats (K h a n n a et al., 1969). Af a q (1970) made botanical identity of this pla~lt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Alkaloids, flavonoids, glycosides, phenol, tannins, coumarin, terpenoids, and quinone were the major phytochemicals detected. Our result concurs with that of Vohora and Kumar 16 and Kazmi et. al.…”
Section: Resultssupporting
confidence: 94%
“…Alkaloids, flavonoids, glycosides, phenol, tannins, coumarin, terpenoids, and quinone were the major phytochemicals detected. Our result concurs with that of Vohora and Kumar 16 and Kazmi et. al.…”
Section: Resultssupporting
confidence: 94%
“…The plant had been tried for several remedial purposes in the past [1,2]. It is also listed in Avicenna's book on cardiac drugs [3]. Avicenna wrote in his book that the drug sets the heart at ease [4].…”
Section: Introductionmentioning
confidence: 99%
“…This can be confirmed from several sources: One of the medical books written by an Ottoman author Hayatizade Mustafa Fevzi Efendi (1641-1693), gives the plant's names, including zarnab, in Turkish, Arabic, Latin and in some other languages (Tuncer, 1978). Authors from India (Vohora and Kumar, 1971) and from Azerbaijan (Alakbarov, 2007) also reported that zarnab is Taxus baccata.…”
Section: Avicenna and His Tract On Cardiac Drugsmentioning
confidence: 93%